EXPRESSION OF THE IDEA OF THE NOVEL IN POLARITY (BASED ON THE NOVEL "KOMILA" BY R. KARIMOV) - Sanobarkhon KARIMOVA (Western European Studies, 2025)
This article analyzes the work of the Uzbek-Kyrgyz writer Rahim Karimov called "Komila". The process of creating a character through the depiction of objects in the composition of the work is studied
Keywords: genre; composition; image; contrast